Pengaruh suhu permukaan laut terhadap hasil tangkapan ikan Tuna Sirip Kuning (Thunnus albacares) di Perairan Barat Sumatera Barat - Cut Intan Zahara; Elizal Elizal; Mubarak Mubarak (Jurnal Zona, 2022)
This study aims to look at fluctuations in sea surface temperature and also the relationship between sea surface temperature and yellowfin tuna catches in West Waters, West Sumatra Province. The research method used is a survey method, namely collecting field data by conducting direct observations, as well as interviews with local fishermen and spatial analysis methods are used to obtain the distribution of sea surface temperatures. The results of this study indicate that the average sea surface temperature in 2019-2021 ranges from 26.99 - 31.21 oC, where the average maximum temperature ranges from 31.21 oC in March 2020 and the average minimum temperature ranges from 26, 99 oC in October 2019. The results of simple linear regression analysis show a correlation coefficient value of 0.857 and a coefficient of determination value of 0.756.